Surgical outcomes of trabeculectomy and glaucoma drainage implant for uveitic glaucoma and relationship with uveitis activity. (27th February 2017) - Kwon, Hye Jin; Kong, Yu Xiang George; Tao, Lingwei William; Lim, Lyndell L; Martin, Keith R; Green, Catherine; Ruddle, Jonathan; Crowston, Jonathan G
Abstract: Importance: This study provides ophthalmologists who manage uveitic glaucoma with important information on factors that can affect the success of surgical management of this challenging disease. Background: This study examines surgical outcomes of trabeculectomy and glaucoma device implant (GDI) surgery for uveitic glaucoma, in particular the effect of uveitis activity on surgical outcomes. Design: Retrospective chart review at a tertiary institution. Samples: Eighty‐two cases with uveitic glaucoma (54 trabeculectomies and 28 (GDI) surgeries) performed between 1 December 2006 and 30 November 2014. Methods: Associations of factors with surgical outcomes were examined using univariate and multivariate analysis. Main Outcome Measures: Surgical outcomes as defined in Guidelines from World Glaucoma Association. Results: Average follow up was 26.4 ± 21.5 months. Overall qualified success rate of the trabeculectomies was not statistically different from GDI, being 67% and 75%, respectively ( P  = 0.60). Primary and secondary GDI operations showed similar success rates. The most common postoperative complication was hypotony (~30%). Active uveitis at the time of operation was higher in trabeculectomy compared with GDI group (35% vs . 14%). Active uveitis at the time of surgery did not significantly increase risk of failure for trabeculectomies. Recurrence of uveitis was significantly associated with surgical failure in trabeculectomy group (odds ratio 4.8, P  = 0.02) but not in GDI group. Conclusions and Relevance: Surgical success rate of GDI was not significantly different from trabeculectomy for uveitic glaucoma in this study. Regular monitoring, early and prolonged intensive treatment of ocular inflammation is important for surgical success particularly following trabeculectomy.